Improving the adoption of a school-based nutrition program: findings from a collaborative network of randomised trials - Courtney Barnes; Rachel Sutherland; Lisa Janssen; Jannah Jones; Katie Robertson; Justine Gowland-Ella; Nicola Kerr; Aimee Mitchell; Karen Gillham; Alison L. Brown; Luke Wolfenden (Implementation Science)
Abstract Background Public health nutrition interventions, including school-based programs, are a recommended approach to improve child dietary behaviours. However, the adoption of effective school-based nutrition programs face numerous challenges, including the limited evidence on effective strategies to maximise implementation and adoption of such programs. This study aimed to address this evidence gap by employing a novel collaborative network trial design to evaluate a series of implementation strategies employed by three NSW Local Health Districts, to improve school adoption of an effective school-based nutrition program (‘SWAP IT’). Methods Three independent, two arm parallel group randomised controlled trials were conducted simultaneously to examine the potential effectiveness of implementation strategies on school adoption of SWAP IT. Schools were randomised to either a high intensity (various implementation strategies), or a business as usual (minimal support) group. Measures and data collection processes were harmonised across the three trials to provide individual school-level data for planned pooled analyses. The primary outcome was school adoption of SWAP IT, objectively measured via electronic registration records. Logistic regression analyses were used to assess school adoption of SWAP IT for each trial. Meta-analyses were also conducted to pool the effects of the three trials and allow the comparison of the potential relative effects of the different strategies. Results A total of 287 schools were included in the study: Trial 1 (n = 164), Trial 2 (n = 64) and Trial 3 (n = 59). Relative to control, we found increased odds of adoption in Trial 1 that employed a combination of the educational materials and local facilitation strategies (OR 8.78; 95%CI 2.90, 26.56; p < 0.001), but no significant differences in adoption in Trial 2 or 3 that employed solely the educational materials strategy. Pooled data suggests the combination of educational materials and local facilitation has a greater effect on adoption compared to educational materials alone (OR 4.18; 95%CI 1.60, 10.04; n = 3 studies; indirect effect). Conclusion Findings of this study indicate that local facilitation is an important strategy to increase school adoption of SWAP IT, and potentially other health promotion programs. Trial registration The trials were prospectively registered with Australia New Zealand Clinical Trials Register: ANZCTR, ACTRN12622000257763, Registered 11/2/2022, https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=383515&isReview=true ANZCTR, ACTRN12622000406707, Registered 9/3/2022 https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=383701&isReview=true ANZCTR, ACTRN12622000252718, Registered on 11/2/2022, https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=383513&isReview=true